(3efThQ GdZjHIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOhO bGFe GdOjf Edi Cgd GdQVi hGdJSdje Cgd GdWgGQI hGdJbi hGdSdGeI GdeYJQajf Hhdi GdOjf s
(3BNQgG (B:s
(3hGdSdGe Ydi hdi GdbjGeI GdbGFe HehLHGJ GdHYK hGdfTQ hgh MSH YHOg GdVYja GdQGLi dQMeJg hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B110s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis